2019
DOI: 10.1093/geront/gnz161
|View full text |Cite
|
Sign up to set email alerts
|

Persons With a Migration Background Caring for a Family Member With Dementia: Challenges to Shared Care

Abstract: Background and Objectives By shedding light on the reasons why persons with a migration background (PwM) may take up the role of family caregiver of a person with dementia, and how this relates to gender norms, we aim to elucidate cultural and social dynamics that impede care sharing. Research Design and Methods A qualitative study of 12 PwM who provide care, or have recently provided care, for a family member with dementia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…So it is likely that they were not recruited in adequate numbers. Studies have shown that caregivers with a migration background generally have only limited access to sources of advice and information as well as medical support, so that this group is presumably underrepresented in the present study [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…So it is likely that they were not recruited in adequate numbers. Studies have shown that caregivers with a migration background generally have only limited access to sources of advice and information as well as medical support, so that this group is presumably underrepresented in the present study [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals can support the dignity of informal caregivers of migrant patients by making sure to take them seriously in their caring role, by keeping them fully informed, by helping them build skills in providing good care, and by ensuring education about care and about the patient's disease. Especially when serving migrant patients, care professionals could facilitate a familial approach to help family members share and manage the burden of care [34]. At the same time, they should be alert to feelings and emotions in informal caregivers as caregivers tend not to share these with others [34] as part of their dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially when serving migrant patients, care professionals could facilitate a familial approach to help family members share and manage the burden of care [34]. At the same time, they should be alert to feelings and emotions in informal caregivers as caregivers tend not to share these with others [34] as part of their dignity. Migrant caregivers could likewise be supported by welfare organizations that offer them opportunities to focus on exchanging experiences and building small-scale care skills [26], as well as providing emotional support to caregivers and discussing ways of caring for a loved one and maintaining dignity should a care handover to a nursing home be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of dementia, it is common for 1 person in culturally diverse families to serve as the primary caregiver [3]. As dementia symptoms progress, this primary caregiver may increasingly dedicate their time to caring for the person with dementia, giving up on their own personal activities and social life, which can subsequently result in isolation of the caregiver [37]. The strong feelings of filial or religious duty experienced by these primary caregivers may motivate them to continue to provide informal care despite increasing levels of burden [37].…”
Section: Discussionmentioning
confidence: 99%